The pharmacokinetics of metformin and concentrations of haemoglobin A1C and lactate in Indigenous and non‐Indigenous Australians with type 2 diabetes mellitus. (April 2015) - Duong, Janna K.; Kumar, Shaun S.; Furlong, Timothy J.; Kirkpatrick, Carl M.; Graham, Garry G.; Greenfield, Jerry R.; Williams, Ken M.; Day, Richard O.
Abstract : Aims: To compare the pharmacokinetics of metformin between diabetic Indigenous (Aboriginal and Torres Strait Islander) and non‐Indigenous patients. Methods: An observational, cross‐sectional study was conducted on type 2 diabetic Indigenous and non‐Indigenous patients treated with metformin. Blood samples were collected to determine metformin, lactate, creatinine and vitamin B12 concentrations and glycosylated haemoglobin levels. A population model was used to determine the pharmacokinetic parameters. Results: The Indigenous patients (median age 55 years) were younger than the non‐Indigenous patients (65 years), with a difference of 10 years (95% confidence interval 6–14 years, P < 0.001). The median glycosylated haemoglobin was higher in the Indigenous patients (8.5%) than in the non‐Indigenous patients (7.2%), with a difference of 1.4% (0.8–2.2%, P < 0.001). Indigenous patients had a higher creatinine clearance (4.3 l h −1 ) than the non‐Indigenous patients (4.0 l h −1 ), with a median difference of 0.3 l h −1 (0.07–1.17 l h −1 ; P < 0.05). The ratio of the apparent clearance of metformin to the creatinine clearance in Indigenous patients (13.1, 10.2–15.2; median, interquartile range) was comparable to that in non‐Indigenous patients (12.6, 9.9–14.9). Median lactate concentrations were also similar [1.55 (1.20–1.88) vs. 1.60 (1.35–2.10) mmol l −1 ] for Indigenous and non‐Indigenous patients, respectively. The median vitamin B12 was 306 pmol l −1 (range 105–920 pmol l −1 ) for the Indigenous patients. Conclusions: There were no significant differences in the pharmacokinetics of metformin or plasma concentrations of lactate between Indigenous and non‐Indigenous patients with type 2 diabetes mellitus. Further studies are required in Indigenous patients with creatinine clearance <30 ml min −1 .